A Computational Protein Phenotype Prediction Approach to Analyze the Deleterious Mutations of Human MED12 Gene. Issue 9 (10th February 2016) - Banaganapalli, Babajan; Mohammed, Kaleemuddin; Khan, Imran Ali; Al‐Aama, Jumana Y.; Elango, Ramu; Shaik, Noor Ahmad
ABSTRACT: Genetic mutations in MED12, a subunit of Mediator complex are seen in a broad spectrum of human diseases. However, the underlying basis of how these pathogenic mutations elicit protein phenotype changes in terms of 3D structure, stability and protein binding sites remains unknown. Therefore, we aimed to investigate the structural and functional impacts of MED12 mutations, using computational methods as an alternate to traditional in vivo and in vitro approaches. The MED12 gene mutations details and their corresponding clinical associations were collected from different databases and by text‐mining. Initially, diverse computational approaches were applied to categorize the different classes of mutations based on their deleterious impact to MED12. Then, protein structures for wild and mutant types built by integrative modeling were analyzed for structural divergence, solvent accessibility, stability, and functional interaction deformities. Finally, this study was able to identify that genetic mutations mapped to exon‐2 region, highly conserved LCEWAV and Catenin domains induce biochemically severe amino acid changes which alters the protein phenotype as well as the stability of MED12‐CYCC interactions. To better understand the deleterious nature of FS‐IDs and Indels, this study asserts the utility of computational screening based on their propensity towards non‐sense mediated decay. Current study findings may help to narrow down the number of MED12 mutations to be screened for mediator complex dysfunction associated genetic diseases. This study supports computational methods as a primary filter to verify the plausible impact of pathogenic mutations based on the perspective of evolution, expression and phenotype of proteins. J. Cell. Biochem. 117: 2023–2035, 2016. © 2016 Wiley Periodicals, Inc. Abstract : Computational methods as a primary filter to verify the plausible impact of pathogenic mutations based on the perspective of evolution, expression, and phenotype of proteins.